Cross-Media or Transmedia? Brand Communication across Hong Kong's Flagship Cultural Events - Yang, Shiyao (Transactions on Social Science, Education and Humanities Research, 2026)
Hong Kong has been organising "mega events" that serve as a specific strategy for city branding and intends to become the "Events Capital of Asia"; however, the communication channel through which flagship cultural events construct the city's brand—referred to as "cross-media" in the title of this paper—has not been systematically explored in academic research and is often mistaken for the stronger concept of transmedia branding. The three literatures of transmedia branding, place branding and event studies have been combined to form a four-dimensional analytical framework in this paper, and a comparative qualitative study has been conducted on three Hong Kong flagship cultural events: M+/West Kowloon, the Hong Kong New Year Countdown, and Art Basel Hong Kong. Based on the analysis, most flagship-event communications are still integrated cross-media efforts (a single message transmitted across all channels), rather than true transmedia branding (separate narrative pieces that audiences assemble); only the institution-anchored M+ case is approaching the transmedia end. The difference is due less to budget and reach than to institutional character and narrative resources. According to the above data, Hong Kong's flagship event branding has broader cross-media dissemination but lacks the same narrative richness and is thus considered "content-light" by critics. A portable analytical framework is provided, along with an empirical clarification of a frequently confused distinction.
Keywords: Transmedia branding; cross-media communication; place branding; flagship cultural events; Hong Kong.